ANALYSIS OF THE DEGREE OF ACCESS TO THE EUROPEAN AGRICULTURAL FUND FOR RURAL DEVELOPMENT IN ROMANIA - Georgeta, Paun (Economics of Agriculture, 2012)
Although the mechanisms necessary to adapt the current Common Agricultural Policy, Romania has achieved targets for increasing labor productivity, while increasing market competitiveness and transformation of current structures viable operating structure as the foundation for integration into the common market. These steps can not be bypassed. As the old Member States have long exceeded those steps and it is not possible the unitary development at European level through the maintenance of important differences, the new Member States should be supported to speed up reforms. As a result, the Romanian agriculture, although it will evolve at a European level and in the future will have features related to the nature of climatic and human resources which furthers the quality of products, diversified. This specific development is the expression of diversity of Member States to ensure their national identity. Support the European integration process fosters diversity of each Member State market competitiveness of food products.